STUDI LITERATUR ; PENGARUH MODEL PEMBELAJARAN ROLE PLAYING TERHADAP HASIL BELAJAR SISWA PADA MUATAN PELAJARAN PENDIDIKAN KEWARGANEGARAAN KELAS V SEKOLAH DASAR - Indah Setyani, Luthfi; Suntari, Yustia; Dallion, Engga (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The role playing method is one of the learning methods that allows students to practice putting them selves in various roles and situations that will improve their learning outcomes, understanding and skills. This research is quantitative research using experimental methods, the purpose of this article is to review the literature related to the Effect of Role Playing Learning Model on Student Learning Outcomes in Civics Class V Elementary School. Based on the results of the literature study, it shows that one of the factors that can affect student learning outcomes is the unattractiveness of the learning methods used by teachers when teaching. And there are still many students who think that learning Civics is known as a subject that often emphasizes memorization. Therefore, teachers need to choose interesting learning methods, such as using the Role Playing model